223k views
3 votes
Which expression is equivalent to 42 + 12? 7(6+5) 2(40+6) 6(7+2) 10(32+2)

2 Answers

6 votes

Answer:

6(7+)

Explanation:

1) Start by solving the original equation

42 + 12 = 54

2) Solve the other equations until you find a match

2a) Start with what's in the parenthesis

7(6+5) = 7(11) = 77

2b)

2(40+6) = 2(46) = 92

2c)

6(7+2) = 6(9) = 54

This is your answer

2d)

10(32+2) = 10(34) = 340

User Claya
by
5.7k points
0 votes

Answer: 6(7 +2)

Explanation:

Calculate 42 + 12, which is 54.

Calculate 7(6 + 5), which is 7 * 11 = 77.

Calculate 2(40 + 6), which is 2 * 46 = 92.

Calculate 6(7 + 2), which is 6 * 9 = 54.

Calculate 10(32 + 2), which is 10 * 34 = 340.

And, we can conclude the expression 6(7 + 2) is equivalent to 42 + 12.

User IBog
by
6.1k points